A new species of the genus Ablabesmyia Johannsen from the Neotropics and description of the pupa of Ablabesmyia bianulata Paggi (Diptera: Chironomidae: Tanypodinae) - Siri, Augusto; Paggi, Analía C. (Zootaxa, 2010)
The male, pupa and fourth instar larva of Ablabesmyia platensis sp. n. from La Plata, Buenos Aires province, Argentina and the pupa of A. bianulata Paggi collected in southern Argentina are described and figured. The male adult diagnosis of A. bianulata is emended, and the aedeagal complex is redescribed and photographed. Differences in the aedeagal complex and the color pattern of the pupa mainly distinguish these two species. The new species is also compared with the Neotropical A. oliveirai Oliveira et Gessner.